Could pain understanding by patients help the assessment of trigeminal neuralgia? - Silvia Regina Dowgan Tesseroli de Siqueira; Manoel Jacobsen Teixeira; José Tadeu Tesseroli de Siqueira (Revista Dor)
ABSTRACT BACKGROUND AND OBJECTIVES: To observe the efficacy of pain management by means of an educational proposal to address patients with trigeminal neuralgia, which is a chronic pain with high daily activity limitation rates. METHODS: Eight patients being treated of trigeminal neuralgia participated in weekly meetings on pain in a general reference hospital. Patients had uncontrollable pain in spite of treatments so they would come very frequently to the hospital (once every one or two weeks). Patients were invited to participate in a series of meetings (four) to receive information and discuss about the disease and pain. RESULTS: There has been increased interval between appointments for two patients, who went from weekly to biannual visits, and six patients were discharged with controlled symptoms. CONCLUSION: Education on pain has helped its management and coping by patients, by means of understanding their condition, in addition to improving their abilities to deal with it, decreasing hospital visits due to less pain recurrence.